The Emotional Life of Contemporary Public Memorials : Towards a Theory of Temporary Memorials - Doss, Erika (2008)
From the commemoration of September 11 to the Holocaust memorial in Berlin, recent decades have witnessed a substantial increase in the number of new public memorials built in both Europe and the United States. This volume considers the contemporary explosion of public commemoration in terms of changed cultural and social practices of mourning, memory, and public feeling. Positing memorials as the physical and visual embodiment of our affective responses to loss, Erika Doss focuses especially on the memorial ephemera of flowers, candles, balloons, and cards placed at sites of tragic death in order to better comprehend how grief is mediated in contemporary commemorative cultures. De laatste jaren neemt het aantal publieke gedenkplaatsen in Europa en de VS enorm toe. Met bloemen, kaarsen, ballonnen, handgeschreven berichten en pluche beesten, creeëren we tijdelijke gedenkplaatsen om zo een tragische of traumatische dood te verwerken. In The Emotional Life of Contemporary Public Memorials gaat Erika Doss in op deze explosie van publieke gedenkingen. Ze neemt daarbij nieuwe rituelen van rouw, herinnering en publieke gevoelens in beschouwing. Gedenkplaatsen, zo stelt zij, zijn een visuele uiting van publieke affectie. Hun betekenis vraagt om een kennistheorie gebaseerd op historische context, sociale betekenis en emotionele omstandigheden.